Determinação da distância da junção amelocementária à crista óssea alveolar decorridos onze anos do inicio do tratamento ortodôntico - Castro, Luma Oliveira (2019)
Objective: The objective of the present study was to determine, by means of Cone-Beam Computed Tomography (CBCT) images, the distance between the cementoenamel junction and the alveolar bone crest in teeth undergoing orthodontic treatment after 11 years of follow-up. Methodology: Dental CBCT images of patients undergoing orthodontic treatment (T1) were selected from a database. The reference points for the measurements were the cementoenamel junction and the buccal and palatal / lingual alveolar bone crest, being determined by navigating the sagittal, axial and coronal sections. With the aid of the software, a vertical straight line was drawn between the two points, and the distance between the cementoenamel junction to the alveolar bone crest of the buccal (n = 379) and palatal / lingual (n = 379) faces obtained in millimeters. At follow-up after 11 years, the distance from the cementoenamel junction to the alveolar bone crest was again measured following the protocol previously described (T2). Results: After 11 years, there was an increase in the distance from the cementoenamel junction to the alveolar bone crest in all dental groups evaluated. From the total of 758 faces evaluated, 81% (614) presented increased distance when compared to the initial. The buccal face of the lower canines showed the highest frequency of enlargement (91%). In the initial sample, 117 (15%) faces presented a distance greater than 2 mm, while 11 years later, 327 (43%), and the canine buccal face was the one with the highest frequency. Conclusion: The results of the present study showed that 11 years after the beginning of orthodontic treatment, there was an increase in the distance from the cementoenamel junction to the alveolar bone crest in all dental groups evaluated.